A Review of PPP-Adjusted GDP Estimation and its Potential Use for the Fund's Operational Purposes - Wagner, Nancy (Washington, D.C. : International Monetary Fund, 1995)
International comparison of economic aggregates, expressed in domestic currencies, requires their conversion into a common numeraire currency such as the U.S. dollar or the SDR. Since market (or official) exchange rates are subject to fluctuations which may result in comparisons that do not reflect cross-country differences in real economic activity, it is often recommended that purchasing power parity (PPP) rates be used for conversion instead of exchange rates. It is generally agreed that PPP rates are conceptually appropriate conversion factors. However, their practical implementation raises questions regarding the quality of the PPP indices which are currently available. This paper reviews the data and methodology underlying the construction of PPP indices, with particular emphasis on the PPP-based estimates of GDP used in the Fund's World Economic Outlook and the World Bank's World Development Report, and examines some of the issues associated with the use of such PPP-based estimates of GDP for the Fund's operational purposes (such as quota calculations or determination of SAF or ESAF eligibility).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet